Pregnancy outcome in women with sickle cell disease/trait in a tertiary care hospital Nagpur, Maharashtra India: a descriptive cross sectional study - Kose, Varsha; Kose, Saurabh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy in sickle cell women has numerous obstetrical, nonobstetrical and fetal complications. Our objective was to study the pregnancy outcome in women with sickle cell disease/trait. Methods: A descriptive cross sectional study in 2 years study period was conducted. 57 women with sickle cell disease/trait were identified. They were attending the antenatal clinic and were admitted in obstetric ward and followed till 7 days after delivery. Results: Out of total 57 women 49 women (85.96%) were sickle cell trait (AS pattern) and 8 women (14.03%) were sickle cell disease (SS pattern). In women with sickle cell trait Pregnancy induced hypertension was the most common complication. Anaemia and hypothyroidism was the common associated medical problem. 5 babies need NICU admission, 6 babies PBU admission and 33 babies given to mother side just after birth. In women with sickle cell disease severe anaemia, preeclampsia, oligohydramnios and intrauterine growth restriction, lower segment caesarean section for preterm baby was the most common complication. 1 baby required NICU admission, 5 babies require PBU admission and only 2 babies given to mother just after delivery. There were no maternal mortality and neonatal mortality. Conclusions: Maternal morbidity and neonatal morbidity is more in sickle cell disease women. They require early diagnosis, premarital and preconceptional counselling, good multidisciplinary obstetrics and neonatal care and early referral to higher centre.